AUTOLOGOUS STEM CELL TRANSPLANTATION FOR CHRONIC LYMPHOCYTIC LEUKEMIA STILL A VALID TREATMENT OPTION, OR IS THE GAME OVER ? - Fabienne McClanahan; Peter Dreger (Mediterranean Journal of Hematology and Infectious Diseases)
Chemoimmunotherapy with fludarabine, cyclophosphamide, and rituximab (FCR) has been established as the current standard of care for young and fit patients with chronic lymphocytic leukemia (CLL). In the early nineties of the last century, long before the advent of fludarabine or antibody-based strategies, there was realistic hope that myeloablative therapy followed by autologous stem cell transplantation (autoSCT) might be an effective and potentially curative front-line treatment option for suitable patients with CLL. Since then, several prospective trials have disenthralled this hope: although autoSCT can prolong event and progression-free survival if used as part of early front-line treatment, it does not improve overall survival, while it is associated with an increased risk of late adverse events such as secondary malignancies. In addition, autoSCT lacks the potential to overcome the negative impact of biomarkers that confer resistance to chemotherapy or early relapse. The role of autoSCT has also been explored in the context of FCR, and it was demonstrated that its effect is inferior to the currently established optimal treatment regimen. In view of ongoing attempts to improve on FCR, promising clinical activity of new substances even in relapsed/ refractory CLL patients, exciting novel cell therapy approaches and advantages in the understanding of the disease and detection of Minimal Residual Disease (MRD), autoSCT has lost its place as a standard treatment option for CLL.